HUBUNGAN KEBIASAAN MAKAN PAGI DENGAN KEJADIAN ANEMIA PADA MURID SMK AL WASHLIYAH 13 KOTA TEBING TINGGI - Istanul Badiri; Khairunnisa Khairunnisa (Jurnal Sains Riset, 2021)
Anemia is a condition where the number of red blood cells or hemoglobin (Hb) levels in red blood cells is less than the normal limit. Red blood cells contain hemoglobin which will carry oxygen and other nutrients such as vitamins and minerals to the brain and throughout the body. Anemia can cause insufficient blood to bind and carry oxygen from the lungs throughout the body. If the oxygen needed is insufficient, it will result in difficulty concentrating so that the learning process decreases, physical endurance decreases, easily hurts because of low endurance. This study aims to determine the relationship of breakfast habits with the even of anemia in students at Vocational High School Al Washliyah 13 Tebing Tinggi City. The method used in this research is analytic method with cross-sectional research design. The sample in this study were 30 respondents with proportional random sampling. Retrieval of data using questionnaire and manual check. Data analysis with Chi Square test. The results of this study indicate the P value is smaller than the Î± value (0.038 0.05). This means there is a relationship between breakfast habits with the even of anemia in students at Vocational High School Al Washliyah 13 Tebing Tinggi City.Keywords: Breakfast Habits, Anemia, Teenagers